THE TEACHER’S TECHNIQUES FOR BUILDING STUDENTS’ SPEAKING SKILL ON THE BEGINNING OF PANDEMIC COVID 19 - Umar, Vebrianti; Perdana, Indra; Wihastyanang, Wardani Dwi (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
Techniques are important thing for building students’ speaking skills. Therefore the teacher should have techniques and should be able to apply them correctly. Many researchers have discussed about this topic with different tittle actually. This study aimed to find out the techniques used by the teacher for building students’ speaking skill at the tenth grade of SMA Negeri 1 Karang Intan on the beginning of pandemic covid 19. Furthermore, the researcher would like to gain more knowledge about how the teacher applies the techniques, then what the advantages and disadvantages of them. The researcher uses qualitative as the method for conducting this research with English teacher itself as the subject. The researcher collects the data through interview, documentation and observation. The data is analyzed by using Miles and Hubberman’s theory.The result shows the teacher uses stimulation, telling story, discussion, and picture describing as the techniques. The English teacher applies the techniques in different ways. Stimulation:  greeting and giving questions, telling story: experience story and short narrative story, discussion: update news, and picture describing: family picture. Furthermore, these techniques have their own advantages and disadvantages.